Dabrafenib in patients with BRAFV600E-positive advanced non-small-cell lung cancer: a single-arm, multicentre, open-label, phase 2 trial. Issue 5 (May 2016) - Planchard, David; Kim, Tae Min; Mazieres, Julien; Quoix, Elisabeth; Riely, Gregory; Barlesi, Fabrice; Souquet, Pierre-Jean; Smit, Egbert F; Groen, Harry J M; Kelly, Ronan J; Cho, B C; Socinski, Mark A; et al.
Summary: Background: Activating BRAF V600E (Val600Glu) mutations are found in about 1–2% of lung adenocarcinomas, which might provide an opportunity for targeted treatment in these patients. Dabrafenib is an oral selective inhibitor of BRAF kinase. We did a trial to assess the clinical activity of dabrafenib in patients with advanced non-small-cell lung cancer (NSCLC) positive for the BRAF V600E mutation. Methods: In this phase 2, multicentre, non-randomised, open-label study, we enrolled previously treated and untreated patients with stage IV metastatic BRAF V600E -positive NSCLC. Patients received oral dabrafenib 150 mg twice daily. The primary endpoint was investigator-assessed overall response, which was assessed in patients who had received at least one dose of dabrafenib; safety was also assessed in this population. The study is ongoing but not enrolling patients in this cohort. This trial is registered withClinicalTrials.gov, numberNCT01336634 . Findings: Between Aug 3, 2011, and Feb 25, 2014, 84 patients were enrolled, six of whom had not previously received systemic treatment for NSCLC. 26 of the 78 previously treated patients achieved an investigator-assessed overall response (33% [95% CI 23–45]). Four of the six previously untreated patients had an objective response. One patient died from an intracranial haemorrhage that was judged by the investigator to be due to the study drug. Serious adverse events were reported in 35 (42%) of 84 patients. The most frequent grade 3 or worse adverse events were cutaneous squamous-cell carcinoma in ten (12%), asthenia in four (5%), and basal-cell carcinoma in four (5%). Interpretation: Dabrafenib showed clinical activity in BRAF V600E -positive NSCLC. Our findings suggest that dabrafenib could represent a treatment option for a population of patients with limited therapeutic options. Funding: GlaxoSmithKline.